Memoir Radin Umar Radin Sohadi aku dan amanah-Mu - Radin Umar Radin Sohadi 1960-2013 (Penerbit Universiti Putra Malaysia, 2014)
Autobiography of Radin Umar Radin Sohadi, the academician of Universiti Putra Malaysia.